Efficacy of Subantimicrobial Dose Doxycycline for Moderate-to-Severe and Active Graves' Orbitopathy. (29th June 2015) - Lin, Miaoli; Mao, Yuxiang; Ai, Siming; Liu, Guangming; Zhang, Jian; Yan, Jianhua; Yang, Huasheng; Li, Aimin; Zou, Yusha; Liang, Dan
Abstract : Aim. To study the efficacy and safety of subantimicrobial dose (SD) doxycycline(50 mg/d) in patients with active and moderate-to-severe Graves' orbitopathy (GO). Methods. Thirteen patients with active and moderate-to-severe GO received once daily oral doxycycline (50 mg/d) for 12 wk. Treatment response at 24 wk was used as the primary outcome, measured by a composite of improvement in Clinical Activity Score (CAS), diplopia, motility, soft tissue swelling, proptosis, and eyelid aperture. Secondary outcome was the change of quality of life score (QoL, including visual functioning subscale and appearance subscale). Adverse events were also recorded. Results. Overall improvement was noted in eight out of 13 patients (61.5%, 95% CI 31.6%–86.1%). Both CAS and soft tissue swelling significantly ameliorated in eight patients at 24 wk. Five patients (38.5%) had improvement in ocular motility of ≥8 degrees. Eyelid aperture (46.2%) also decreased remarkably. For QoL, a significant improvement in appearance subscale (P = 0.008 ) was noted during the study, whereas no difference was observed in visual functioning subscale (P = 0.21 ). Two patients reported mild stomachache at 12 wk. Conclusions. SD doxycycline appears to be effective and safe for the treatment of active and moderate-to-severe GO. It might serve as a new promising therapeutic strategy for GO. This trial is registered withNCT01727973 .